NÚMEROS COMPLEXOS E GEOMETRIA PLANA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
Complex numbers have applications both in mathematics and in other areas of knowledge. But in high school, at which time the student begins the study of this set of numbers, they are taught with emphasis on algebraic manipulations, leaving only the geometric applications reduced the representation of points in the complex plane. In many cases, even this geometric application is addressed. This work aims to address the set of complex numbers using the geometry, enhancing the visualization of some results in GeoGebra, to provide more meaningful to the student learning.
Keywords: números complexos; geometria; aplicações geométricas; complex numbers; geometry; geometrical applications; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA